2020
DOI: 10.1021/acsomega.0c02886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mutations in the Phenamacril-Binding Site of Fusarium Myosin-1 on Its Motor Function and Phenamacril Sensitivity

Abstract: Phenamacril is a Fusarium -specific fungicide used for Fusarium head blight management. The target of phenamacril is FgMyo1, the sole class I myosin in Fusarium graminearum . The point mutation S217L in FgMyo1 is responsible for the high resistance of F. graminearum to phenamacril. Recent structural studies have shown that phenamacril binds to the 50 kDa cleft of the FgMyo1 motor domain, forming extensive interactions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Phenamacril was a commercial fungicide and exhibited excellent antifungal activity against G. zeae with a clear mechanism of action (a specific inhibitor of FgMyo1, not on the cell membrane) . Based on the experimental results, it was found that phenamacril did not have any effect on the cell membrane, but the target compound Y 47 could damage the cell membrane by causing peroxidation of cellular lipids in a concentration-dependent manner, which was consistent with the SEM and FM analyses.…”
Section: Resultssupporting
confidence: 75%
“…Phenamacril was a commercial fungicide and exhibited excellent antifungal activity against G. zeae with a clear mechanism of action (a specific inhibitor of FgMyo1, not on the cell membrane) . Based on the experimental results, it was found that phenamacril did not have any effect on the cell membrane, but the target compound Y 47 could damage the cell membrane by causing peroxidation of cellular lipids in a concentration-dependent manner, which was consistent with the SEM and FM analyses.…”
Section: Resultssupporting
confidence: 75%
“…A previous co‐sedimentation assay of PHA‐actomyosin by Ni et al . has told the same story 39 that PHA could slightly reduce the actin‐pelleted ATP‐bound FgMyo1 IQ2 while not affecting the interaction of non‐ATP‐bound FgMyo1 IQ2 with actin, which may be due to the binding preference of PHA with nucleotide‐bound state myosin, just like blebbistatin does 38,40 …”
Section: Resultsmentioning
confidence: 97%
“…6(f)), where the PHA reduced the amount of actinprecipitated FgMyoI in the presence of ATP, indicating its ability to the dissociation of FgMyoI from F-actin. A previous cosedimentation assay of PHA-actomyosin by Ni et al has told the same story 39 that PHA could slightly reduce the actin-pelleted ATP-bound FgMyo1 IQ2 while not affecting the interaction of non-ATP-bound FgMyo1 IQ2 with actin, which may be due to the binding preference of PHA with nucleotide-bound state myosin, just like blebbistatin does. 38,40 3.4 Weakened swing of the CLD upon phenamacril binding Evident rotation of the CLD was identified in the holo-ATP system based on the RMSF and PCA (mainly PC1) analyses, but the movement was significantly attenuated in the presence of PHA (Figs 2 (a) and 3(a),(b)).…”
Section: The Observation Of Widening Of Myosin Outer Cleft and Decrea...mentioning
confidence: 91%
“…The findings from our group demonstrated that the E198A or E198K substitutions of β 2 ‐tubulin cause high‐level or low‐level resistance of F. graminearum to benzimidazoles, respectively 27,34 . The different amino acid substitutions in the same codon caused a conformational change in the three‐dimensional structures of target proteins, which affected the affinity between the fungicide molecule and target proteins, thereby resulting in differences in fungicide sensitivity 35,36 …”
Section: Discussionmentioning
confidence: 94%
“…27,34 The different amino acid substitutions in the same codon caused a conformational change in the three-dimensional structures of target proteins, which affected the affinity between the fungicide molecule and target proteins, thereby resulting in differences in fungicide sensitivity. 35,36 In addition to S217P or I424S substitutions, other resistant mutation genotypes have also been reported in Fusarium species. In F. asiaticum, point mutations A135T, V151M, P204S, I434M, A577T, R580G/H and I581F from laboratory-induced mutants resulted in low-level resistance, point mutations S418R, I424R, and A577G were responsible for moderate-level resistance, and point mutations K216R/E, S217L, and E420K/G/D conferred highlevel resistance.…”
Section: Discussionmentioning
confidence: 99%